Development of Health Education Booklet on Heart Failure for Public Readers - H, Syafiqah; A, Nurul; S, Nurul; SA, Nur; Sani, Huzairi (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: Heart failure is a condition that is commonly seen in the community, however, there is still a major gap in understanding the diagnosis. This is our effort to spread awareness and share key information on heart failure to patients and carers by a printable booklet as a platform for the public to increase their knowledge about heart failure during the COVID-19 pandemic. Methods. A literature review from clinical guidelines and established medical websites’ information was gathered and made in a concise manner, suitable for public understanding. A designed booklet was filled with essential information and images for reference. Results. A 21-pages reading material with coloured images was divided into sections describing heart failure, types and classification, its management as well as lifestyle modifications. The first section includes cardiac anatomy, physiological function and definition of heart failure. The prevalence in Malaysia was highlighted and compared to the other countries. The leading causes of heart failure in adult Malaysians are ischaemic heart disease (68%), valvular/rheumatic heart disease (29%), and nonischaemic cardiomyopathy (28%). Heart failure is a significant cause of hospitalisation, accounting for approximately 6% to 10% of all acute medical admissions in Malaysia. The list of investigations and types of treatment were included for a better understanding of each management. Patients’ understanding of the disease and lifestyle modification is essential, which will prevent hospital admission and improve clinical outcomes. Conclusion. Information shared through the booklet about the condition of heart failure and its effect on people's life was hoped to assist patients to manage their heart failure better. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S37